2020
DOI: 10.3389/fcimb.2020.00497
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation and Antimicrobial Resistance Profiles of Salmonella Isolated From Breeder Chicken Hatcheries in Henan, China

Abstract: The emergence of antimicrobial-resistant (AR) Salmonella has a major concern worldwide. This study was designed to determine the AR profiles and serovars distribution of Salmonella enterica isolated from different breeds of breeder chickens in the province of Henan, China. For this, 2,139 dead embryo samples were collected from 28 breeder chicken hatcheries, representing two domestic and four foreign breeds. The samples were subjected to the isolation and identification of Salmonella by PCR. The confirmed stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 58 publications
10
47
1
Order By: Relevance
“…Serotyping is an effective approach to evaluating modes of transmission to develop strategies for preventing disease spread within poultry facilities (30). We found that S. Thompson, which is a member of Salmonella serogroup C1 commonly associated with disease in humans (31) and isolated in poultry and poultry eggs (8,28,32), was the most prevalent isolate in the present study. This is in contrast to studies in Shanghai and Sichuan that had identified S. Enteritidis as the most common serovar in commercial chicken farms (25,33), while S. Indiana was found to be dominant in Shandong (34), and S. Weltevreden was dominant in Central Vietnam (35).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Serotyping is an effective approach to evaluating modes of transmission to develop strategies for preventing disease spread within poultry facilities (30). We found that S. Thompson, which is a member of Salmonella serogroup C1 commonly associated with disease in humans (31) and isolated in poultry and poultry eggs (8,28,32), was the most prevalent isolate in the present study. This is in contrast to studies in Shanghai and Sichuan that had identified S. Enteritidis as the most common serovar in commercial chicken farms (25,33), while S. Indiana was found to be dominant in Shandong (34), and S. Weltevreden was dominant in Central Vietnam (35).…”
Section: Discussionsupporting
confidence: 48%
“…We found that S . Thompson, which is a member of Salmonella serogroup C1 commonly associated with disease in humans ( 31 ) and isolated in poultry and poultry eggs ( 8 , 28 , 32 ), was the most prevalent isolate in the present study. This is in contrast to studies in Shanghai and Sichuan that had identified S .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…All (80) Salmonella isolates found multidrug-resistant. In agreement with this study, the zoonotic Salmonella isolates were developed multidrug resistance in Modjo, 20 Gondar, 7 Jimma, 9 and China, 8 Morocco. 29 This multidrug resistance might be attributed to the irrational use of antibiotics practiced in the area 30 , 31 and/or the evolutionary nature of Salmonella species.…”
Section: Discussionsupporting
confidence: 88%
“…15,16 Before this research, many other types of research were conducted to assess the resistance pattern of Salmonella both in human and animals, but due to the "evolutionary nature of the bacteria and the dependency of patients to antibiotics", the resistance level of Salmonella to antibiotics has been increasing. [6][7][8][9][17][18][19][20] Antibiotic resistance surveillance of foodborne pathogens in food animals like sheep is strongly recommended to mitigate the global crises due to AMR and there was no surveillance had been done yet in the study area.…”
Section: Introductionmentioning
confidence: 99%